HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN DENGAN KONSEP DIRI - Lina Novita; Elly Sukmanasa; Devi Cahya (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
RELATIONSHIP USING LEARNING MEDIA WITH SELF CONCEPTThe aim of this study is to determine the relationship between the use of learning media and self-concept. The research approach uses quantitative with correlational study methods. The study data was obtained using a questionnaire tool for both variables. The validity test of the use of instructional media and self-concept tools was calculated using the Pearson Product Moment formula and the reliability coefficient was calculated using the Cronbach Alpha formula. The population consisted of VA, VB and VC students from the District 2 Primary School. A sample of 48 students was obtained using the Taro Yamane formula. Testing the analysis requirements in the form of normality tests (Liliefors). After the normality test is performed, a homogeneity test is then performed (Fisher). Data declared normal and homogeneous are used to test hypotheses, the results of which indicate that the use of instructional media has a positive and significant relationship with self-concept. Statistical analysis yields a correlation coefficient (rxy) of 0.69, which means that the relationship level is classified as strong and a count of 8.80 is higher than ttable with a significant level of 0.05 of 2.021, meaning significant. It can therefore be concluded that there is a positive and significant relationship between the use of instructional media and the self-concepts of students.